Empowering PKK Women' Group Based on Local Potential of Moringa Plants (Moringa Oleifera Lam) Through Product Innovation in Aceh Besar: Pemberdayaan Kelompok Ibu PKK Berbasis Potensi Lokal Tanaman Kelor (Moringa Oleifera Lam) Melalui Inovasi Produk Di Aceh Besar - Aryani, Irma; Syarifah Farissi Hamama; Anzora, Anzora; Rahmi, Rahmi; Saifullah, Saifullah; Wiza Salvira (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Moringa is a plant that has high nutritional content in its leaves, stems and fruit. Moringa leaves can be used as a basic ingredient for processing food, drinks or medicines. This service activity empowers 15 PKK women from Lamleuot Village, Cot Glie Aceh Besar District, in processing Moringa leaves into innovative and marketable products. The Community Partnership Empowerment (PKM) activity aims to empower the potential of women through product innovation from Moringa leaves in order to improve the welfare/economy of their families so that an economically independent society is formed. The method used in this service is a workshop providing material related to entrepreneurship, business management, training and direct practice. This activity has trained partners to process Moringa leaves into products in the form of tea, capsules, meatballs, cookies and pudding. Based on the evaluation results, it shows that there has been an increase in partners' knowledge and understanding of business management and moringa processing, as well as achieving success indicators.